2022
DOI: 10.1021/acs.jchemed.1c01240
|View full text |Cite
|
Sign up to set email alerts
|

Three Steps to an Inclusive Education: MiC, a Model for Inclusive Chemistry Teaching

Abstract: The acquisition of scientific knowledge through problem solving offers the possibility to consider different requirements for inclusive chemistry lessons. The architecture of the “model for inclusive chemistry teaching” (MiC) is designed in a way that teachers can derive concrete, planning-guiding assistance from it. Following this model, we designed a learning environment “Fire & Flame” with real experiments, an interactive Multitouch Learning Book (a dynamic, web-based platform that allows the instructor to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Brazilian Journal of Development, Curitiba, v.9, n.3, p. 10567-10578, mar., 2023 growth of research on inclusive strategies has been observed in the literature 28,29,[38][39][40][41][42][43][44][45][46][47]30,[48][49][50][31][32][33][34][35][36][37] ; however, there needs to be more illustrative models to guide students and teachers, which is where TBM comes into play.…”
Section: Tbm As a New Shape Of Chemical Educationmentioning
confidence: 99%
“…Brazilian Journal of Development, Curitiba, v.9, n.3, p. 10567-10578, mar., 2023 growth of research on inclusive strategies has been observed in the literature 28,29,[38][39][40][41][42][43][44][45][46][47]30,[48][49][50][31][32][33][34][35][36][37] ; however, there needs to be more illustrative models to guide students and teachers, which is where TBM comes into play.…”
Section: Tbm As a New Shape Of Chemical Educationmentioning
confidence: 99%